Lean startup and its application in business and operations strategy: empirical studies - Kola, Mohamed Nadeem (My University, 2018)
Lean startup is a new concept that was initially developed to help startups grow their business in a more effective and scientific way. The methodology has some elements that are in contrast to the way businesses or new ventures are traditionally run. While the lean startup methods have been proven in industry, the academic research especially within a South African context has been minimal. The purpose of this study is to evaluate the extent to which lean startup principles have been applied across industry in South Africa and how these have been used in conjunction with the corporate and operations strategy. From the research it was found that while South African professionals may be familiar with the concept, the application of the concept in its full form is limited. Participants also at times applied the concepts without having full awareness that the concepts were part of the lean startup methodology. A number of participants used the methodology to help develop the business and operations strategy. Participants also typically saw the value in the concepts for application across industry as long as the right structures are in place to help support the initiative.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Masters of Science in Engineering. 9 August 2019
Keywords: Success in business--South Africa; Entrepreneurship